UJI EFEKTIFITAS BERBAGAI KONSENTRASI EKSTRAK DAUN KELOR (Moringa oleifera Lam.) DALAM MENGHAMBAT PERTUMBUHAN PATOGEN (Alternaria sp.) PENYEBAB PENYAKIT BERCAK COKELAT PADA TANAMAN TOMAT: Effectiveness Test of Moringa Leaf Extract (Moringa oleifera lam.) In Inhibiting Growth of Alternaria sp. Causal of Brown Spot Disease in Tomato Plants - Intan jayanti; Jahuddin, Rahmat; Irawanti Azis, Asti (Fakultas Pertanian Universitas Islam Makassar, 2025)
Brown spot disease Alternaria sp. It is a big obstacle because it can reduce the production of tomato plants by 5-78%. This study aims to determine the most effective concentration of moringa leaf extract in inhibiting growth (Alternaria sp.). This research was carried out from November 2024 to March 2025. This study used a complete random design (RAL) consisting of 2.5% moringa leaf extract (P1), 5% moringa leaf extract (P2), moringa leaf extract 7.5% (P3), moringa leaf extract 10% (P4), and Control (P0). The results showed that moringa leaf extract with a concentration of 10% which had a better effect in suppressing the growth of mushrooms (Alternaria sp.).